Integrasi Media Sosial sebagai Alat Pembelajaran di Madrasah Ibtidaiyah SWASTA MAMBA’UL ‘ULUM - Jafar Rambe (Insan Zenius Ilmiah, 2024)
This study focuses on children's developmental progress at Raudhatul Athfal Al-Bashitiyah concerning learning activities in early childhood education RA Al-Basithiyah, specifically in group B, where the children's numerical recognition skills are notably deficient. When requested, numerical figures should be displayed in the corresponding forms of the digits. Furthermore, only 13 youngsters can write the digits 1-10, while only 17 children can sequentially recite the numbers 1-10. The children's incapacity at RA Al-Basithiyah to recognize and recite the numbers 1-10 is due to the suboptimal teaching method employed for number recognition. The introduction of numbers needs to be supported more by modest learning material, which fails to enhance children's number recognition skills. This study seeks to ascertain if using number cards as a medium can improve children's counting abilities at RA Al Bashitiyah. This study constitutes a Classroom Action Research (PTK). This research employs observation and documentation as data-collecting tools. The participants in this study are the offspring of RA Al Bashitiyah. The study's results utilized two cycles: in the first cycle, the MB category comprised 18 children (60%) and the BSH category included 12 children (40%); in the second cycle, the MB category contained two children (7%) while the BSB category encompassed 28 children (93%), indicating the completion of the second cycle. The number card game enhances children's counting abilities